Role of Aahara and Vihar in Life Longevity with special reference to Prakriti - Rohit Kumar Patel; Sonali Muwel (AYUSHDHARA, 2024)
Ayurveda takes a comprehensive approach, taking into account all the variables that are auxiliary in determining health. Originally from India, this age-old field of medicine and positive health is still useful in today’s world. The ideas of Tridosha and Prakriti are central to Ayurvedic philosophy. It is the Tridoshas (Pitta, Kapha, and Vata) that maintain normal bodily processes. Diseases are caused by imbalances in Tridoshas brought on by poor diet and lifestyle choices. Ayurveda states that a description of a person’s physical, physiological, and psychological makeup constitutes their psychosomatic constitution, also referred to as Deha Prakriti. One of the most crucial ideas was chosen at the moment of conception and is known as Prakriti. Prakriti is the constitution of the organism. Ayurveda places a strong focus on a healthy person’s Aahar-Vihar and Nidra, which are essential for a healthy body. In the Sutra sthan, Acharya Charak also places a strong emphasis on prophylaxis, prevention, nutrition, medication, and lifestyle. Sufficient deep sleep, yoga, a pleasant outlook, and healthy Aahar-Vihar are the finest ways to boost the body’s overall life force.